Strength training in pregnancy. Systematic review of benefits and risks - Karol Demel; Antoni Kantor; Jakub Król; Łukasz Bialic; Monika Dziedzic; Sebastian Polok; Adriana Potoczek; Justyna Talaska; Marta Godyń; Dorota Zatłoka-Mazur (Quality in Sport)
Background Strength training during pregnancy has historically been approached with caution, but recent evidence suggests it can be safe and beneficial when properly supervised. This review examines its impact on maternal and fetal health, addressing both advantages and potential risks.